Formulasi Sediaan Sunscreen dari Ekstrak Etanol Daun Ubi Jalar Ungu (Ipomoea batatas L.) - Rosiana Rizal; Salman; Kiki Ariyani (Jurnal Sains Farmasi Dan Kesehatan, 2023)
Ultraviolet rays that have the most influence on skin health are ultraviolet B radiation because they have the strongest effect in causing photodamage to the skin. One way to minimize skin damage from ultraviolet exposure is the need for antioxidant compounds. Ipomoea batatas leaves have potential as antioxidant agents because their phytochemical components are higher than the tuber, contain secondary metabolites of flavonoids, phenolics, saponins and alkaloids. This study aims to determine the ethanolic extract of Ipomoea batatas leaf can be formulated in a cream dosage form that meets the requirements and to determine the difference in the concentration of ethanolic extract of Ipomoea batatas leaf can affect the value of the sun protection factor as a sunscreen. Extracted by maceration of 70% ethanol which was formulated in the form of sunscreen with an extract concentration of 2% (F1), 4% (F2) and 6% (F3) and followed by an in-line SPF test using UV-Vis spectrophotometry. The results of this study indicate that the preparation meets the requirements of organoleptic, homogeneity, pH, dispersibility, adhesion and viscosity during a storage period of 28 days and the measurement results of the preparation with a concentration of 500 ppm at a wavelength of 290-320 nm for each formula. SPF values were obtained at F1 4.4 (moderate protection), F2 5.5 (medium protection) and F3 7.6 (extra protection). This research can be said that the ethanolic extract of purple sweet potato leaves can be formulated in the form of cream preparations and cream preparations at F1, F2 and F3 meet the requirements of a good cream.